Our Surgical Strategy for Adult Spine Deformity with Osteoporosis - Yasuhiro Nakajima (Neurologico Spinale Medico Chirurgico, 2018)
Osteoporosis is a major social problem in Japan, which is becoming a super-ageing society. Spinal deformity in the elderly causes various symptoms such as neurological deficits, pain, gastroesophageal reflux disease, etc., which impair QOL of the patients. Osteoporosis is one of major etiologies for elderly spinal deformity. At the same time, osteoporosis often causes serious problems in surgical treatment for elderly spinal deformity including instrumentation failure, proximal and distal junctional kyphosis, etc. This presentation will summarize our surgical strategy for prevention of instrument failure, including our original surgical techniques and osteoporosis treatments.